Prawo a sprawiedliwość w procesie sądowej interpretacji norm prawa do świadczeń rodzinnych - Kościuk, Dominik J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article aims to draw attention to the problem of ‘omitting’ the literal content of the law by administrative courts and focusing on the idea of justice and equality. This problem is particularly visible in relation to the issue of social benefits. It can lead to a disturbance of the sense of law uniformity and clarity among citizens.
Keywords: family benefits; legal interpretation; administrative judgements; justice; public administration